Private Capital Formation Activities and Bank Credit Access Among Farmers in Zimbabwe - Chigunhah, Blessing Ropafadzo; Svotwa, Ezekia; Munyoro, Gerald; Mabvure, Tendai J.; Govere, Ignatius (International Journal of Economics and Financial Issues, 2020)
Bank credit is indispensable for commercializing and modernizing the agricultural sector in developing economies like Zimbabwe, where agriculture is the key pillar of livelihoods. This study sought to establish the relative importance of private capital formation activities as drivers of bank credit access among farmers in Zimbabwe. A structured questionnaire collected data from a sample of 372 respondents. Garrett's Ranking Technique and SPSS were used to rank the capital formation activities, whilst Friedman Tests (with Wilcoxon's Signed Rank Post-hoc tests) were used to determine the statistical significance of the rankings. Credit history, which falls under social capital was the most important driver of bank credit access among the farmers, followed by agricultural production qualifications and skills. Farm assets and business management skills were the third and fourth most important catalysts of bank credit access, whilst social networks were the least important. Hence, farmers are implored to uphold integrity in honouring their loan obligations consistently, pursue agricultural production and business management skills, and invest in productive physical assets on and off the farm. Policy should also address the land tenure issue to stimulate on-farm capital investments, and intensify knowledge enhancing agricultural extension services to improve agricultural production knowledge among farmers. Keywords: Bank Credit, Credit Access, Investments, Human Capital Formation, Physical Capital Formation, Social Capital Formation JEL Classifications: Q12; Q13; Q14 DOI: https://doi.org/10.32479/ijefi.9751